The position of social work within the child protection and welfare system in Ireland : a history of present 1991-1862 - Skehill, Caroline (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2001)
The objective of this thesis is to examine the present position of social work within the statutory - child protection and welfare system in Ireland. Its aim is to demonstrate the way in which social work has come to occupy central space within this system by recourse to its past. The methodology employed is a history of the present, introduced by Michel Foucault in Discipline and Punish (1977). This approach to history requires that one starts with a question posed in the present and, from this, selects certain periods in the past to return to, in search of answers. Using this methodology, various aspects relating to the development of professional social work in general and social work within the child protection and welfare system in particular are analysed. The periods covered range from 1862-1991. A range of historical material is analysed in this work. These include: running records, minute books and general records of a range of relevant social service organisations; archival material and official publications relating to statutory government departments, most notably the Department of Health; records of a range of social work professional associations and action groups; and interviews with a number of personnel involved in social work and child care at various moments in the past.
Keywords: Sociology Studies, Ph.D.; Ph.D. Trinity College Dublin